Post-pandemic resilience: assessing the role of corporate social responsibility practices in the hotel sector in fulfilling sustainable development goals / Fazreena Mansor ... [et al.] - Mansor, Fazreena; Marwan, Nur Fakhzan; Yahya, Wan Khaltom; Ali, Roslina; Abd Aziz, Nurul Nadia; Suppiah, Ratha Krishnan (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This study explored the sustainable development goals (SDGs) initiatives of eight international hotels in Penang, Malaysia. The objective was to show how the hoteliers have adapted and refocused their corporate social responsibility (CSR) efforts in response to the unique challenges posed by the COVID-19 pandemic and how those measures affect SDGs fulfillment. The study looked at a current phenomenon considered multi-items as data sources collection including press releases, annual reports, magazines, and newsletters which were culled from their respective websites on the internet. The findings of this exploratory and descriptive analysis revealed that the hotel sector exhibited a commitment to the SDGs, but with varying approaches. The hotels under study contributed to all three key areas of sustainability (economic, social, and environmental) and thus covered most of the SDGs. The eight hotels profiled were actively involved in both responsible and sustainable behavior to help lessen their impact on the environment. The findings may be helpful for the hotels who are on the fence about putting the SDGs into action.